2016
DOI: 10.1177/2325967116657535
|View full text |Cite
|
Sign up to set email alerts
|

Kinematics of Shooting in High School and Collegiate Lacrosse Players With and Without Low Back Pain

Abstract: Background:Low back pain (LBP) and motion alterations can occur in athletes who engage in high-speed throwing motions. The relationship between LBP and shooting motion in lacrosse players is not yet known.Purpose:To quantify the effects of LBP on key kinematic parameters of the lacrosse shot and determine the contribution of the severity of LBP on specific kinematic parameters of the shooting motion.Study Design:Controlled laboratory study.Methods:High school and collegiate players (N = 24) were stratified int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 32 publications
2
8
0
Order By: Relevance
“…The shoulders are vulnerable to injury in lacrosse as both contact and regular overhead activities are common. 17,30 Shoulder and clavicle injuries were not unusual in this analysis, comprising 10.8% of high school and 8.9% of collegiate injuries, similar to prior studies (Table 4). 14,30,31 Although it is important to develop proper techniques to protect the shoulder joint while passing or shooting, the most frequent mechanism of injury for shoulder injury at both the collegiate and high school levels was contact with another player, further emphasizing the need for safe contact strategies in this full-contact sport.…”
Section: Type Of Injurysupporting
confidence: 86%
See 1 more Smart Citation
“…The shoulders are vulnerable to injury in lacrosse as both contact and regular overhead activities are common. 17,30 Shoulder and clavicle injuries were not unusual in this analysis, comprising 10.8% of high school and 8.9% of collegiate injuries, similar to prior studies (Table 4). 14,30,31 Although it is important to develop proper techniques to protect the shoulder joint while passing or shooting, the most frequent mechanism of injury for shoulder injury at both the collegiate and high school levels was contact with another player, further emphasizing the need for safe contact strategies in this full-contact sport.…”
Section: Type Of Injurysupporting
confidence: 86%
“…Another group 14 observed competition and practice injury rates of 4.45 and 1.29/ 1000 AEs, respectively, in high school lacrosse players. Although we noted rates of injury similar to those of prior investigators, these comparisons are limited to sparse research on boys' lacrosse that supplied injury rates as opposed to the many authors [15][16][17][18] who reported only specific injuries, patients with injuries presenting to emergency departments, or case studies.…”
Section: Comparison With Previous Research and Changes Over Timesupporting
confidence: 74%
“…Motion capture set-up was based on previously validated methods. 26,27 Motion analysis was captured with a highspeed, 12-camera optical motion capture system (Motion Analysis Corp, Santa Rosa, California). Data were captured at 200 Hz.…”
Section: Pitch Biomechanics Preparationmentioning
confidence: 99%
“…The slight knee extension in high velocity throwers and shooters made be a concomitant movement with the contraction of the quad that is trying to tilt the trunk forward [27][28][29]. This suggests that strengthening the knee extensor muscles may be important for the athlete since a braced lead leg creates angular momentum of the trunk about the trunk's mediolateral and longitudinal axes [30].…”
Section: Top Arm Max Flexionmentioning
confidence: 99%